CONDUCTIVITY AT ALTERNATING CURRENT OF THIN FILMS OF POLYCHLOROPRENE FORMED IN ELECTRIC FIELD - N. N. Komova (Тонкие химические технологии, 2018)
The temperature dependences of conductivity at alternating current (a frequency of 1 kHz) were studied for thin polychloroprene films formed from a solution on metal electrodes having different polarities: anode, cathode and zero potential. It was found that the nature and form of the temperature dependence of the conductivity of the investigated polymer film depends on the method of sample formation. Temperature regions of maximum conductivity were detected. The realization of the heating cycle followed by the film cooling in a limited region between the electrodes under the action of an alternating electric field leads to an increase in the specific conductivity and a shift of the extreme values to the region of lower temperatures. This effect is manifested to the greatest extent for films formed at the cathode. The process of heating and subsequent cooling is of hysteresis nature both for permittivity and for the dielectric loss tangent. The dependence of dielectric loss tangent on permittivity in a rather wide temperature range is inversely proportional. During the analysis of temperature dependences the mechanism of conductivity was studied for polychloroprene thin films at direct and alternating current. The determined activation energies of the polymeric system conductivity change enable concluding that the mechanisms of electric conductivity at direct and alternating current are of similar nature. The extreme values of permittivity may be due to structural alterations in the process of heating. This is confirmed by the data on the temperature dependence of dielectric loss tangent. In order to explain conductivity at direct current a model of dipole traps is offered.